Hemiglosectomy with selective neck dissection in squamous cell carcinoma at tongue - Abul Fauzi; Andri Hardianto; Rahmat Wariz (Journal of Dentomaxillofacial Science, 2016)
Squamous Cell Carcinoma (SCC) is common is a malignant neoplasma originated from epithelial cells. It is usually involving the oral mucosa and underlying tissue of the tongue, hypopharynx, and also larynx. This report discussed about the management of SCC at tongue with hemiglosectomy and selective neck dissection managed in a male, 57 years old who referred with chief complaints of a mass on the tongue measuring 0.5cm that did not heal, Incision biopsy result confirms a squamous cell carcinoma with well differentiated on his tongue with enlarged lymph nodes level I ipsilateral. The patient was hospitalized and hemiglosectomy surgery with selective neck dissection was conducted, with the entire edge of the excision boundary has been free of tumor mass. Hemiglosectomy with selective neck dissection is selected depending on the size of the lesion, location of lesion and metastases occurrence.